Patton in flames : breaching the iron curtain - Australian Design Group; Rowland, Harry; Pinder, Greg.; Nelson, Seigfried; Andriola, Robert (O'Connor, ACT : Australian Design Group, 2000)
"Patton in flames is Australian Design Group's latest game in the World in Flames series. It postulates the cold war heating up into World War III either in 1945 or 1948. The 1945 campaign starts in March 1945 with a prostrate Third Reich being wooed by both sides in an attempt to carry out General Patton's fantasy plan for world domination. The 1948 campaign starts with the Berlin airlift crisis and the first Arab-Israeli war dragging the superpowers in for a final confrontation."--Rule book.
Board game.
Title from box.
Number of players: Up to 6.
Contains 4 x A1 full colour maps (West and East Europe, Asia and the Pacific), 1 x A3 colour USA mini-map, 5 colour countersheets of 200 counters each (1000 counters total), 1 "Patton in Flames" rule book (including players notes, 2 build charts and 2 four-map campaigns), 1 x production circle/sequence of play/optional rules manifest sheet (folded), 2 colour final edition combat charts (folded), 2 ten-sided dice.
Ages: 12 to adult.
Keywords: Board games; War games